PEMANFAATAN YOUTUBE SEBAGAI COMMUNITY ENGAGEMENT KEGIATAN HUBUNGAN MASYARAKAT SKALA MIKRO - Rintulebda Anggung Kaloka (Master of Communication Science Program, Universitas Diponegoro, 2023)
In previous research, the discussion of public relations practices only existed at the level of government public relations, the private sector and public relations consultants as part of organisations that are outside the community itself, so the discussion of the application of public relations practices carried out by micro communities has not been widely published. The purpose of the study in this research is to provide an overview of the application of public relations practices carried out by micro-scale community structures and their relation to community development of the surrounding community. The subject of this research is the management of RT 03/RW 14 Puri Delta Asri who owns the Gulita Production YouTube channel. The method used is an in-depth interview with the head of the neighbourhood. The results of this study found that the YouTube platform can be a medium that strengthens community engagement in the community.